Pseudotumoral colonic form of location of Crohn’s disease - Galarraga, José; Arias, José; de los Santos, Julio (Cirugía del Uruguay, 1975)
The authors report a ca e of Crohn's granulomatous colitis, of 3 pseudotumoral form, exclusively colonic, in a 65-year-old, female patient. She was surgically treated by a right hemicolectomy. Evolution has been favourable up to thP. moment. The diagnosis difficulties of these cases are pointed out, and the most important features of the disease are reviewed.